El plan vallejo en el contexto actual del comercio exterior colombiano (2017)
This paper analyzes the competitiveness of the use of the Vallejo plan tool as an opportunity for Colombian businessmen to enter the international market. This was done with an exploratory phase in which the Vallejo plan is contextualized, its characteristics and benefits . The following is a theoretical framework referring to the main topics to be discussed in the Vallejo plan and the current reality of Colombian foreign trade, which will be the starting point to analyze the application and continuity of this special system of import and export.